Impact of immunological aging on T cell-mediated therapies in older adults with multiple myeloma and lymphoma - Tamas Fulop; Abdullah M Khan; Valentín Ortiz-Maldonado; Marcus Vetter; Rainer Wirth; Fabian Ullrich; Paul J Bröckelmann; Amin T Turki; Elena-Diana Chiru; Bastian von Tresckow; Raul Cordoba; Nina Rosa Neuendorff (Journal for ImmunoTherapy of Cancer)
The treatment landscape for lymphoma and multiple myeloma, which disproportionally affect older adults, has been transformed by the advent of T cell-mediated immunotherapies, including immune checkpoint inhibition, T cell-engaging bispecific antibodies, and chimeric antigen receptor (CAR) T cell therapy, during the last decade. These treatment modalities re-enable the patient’s own immune system to combat malignant cells and offer the potential for sustained remissions and cure for various diseases.Age profoundly affects the physiological function of the immune system. The process of biological aging is largely driven by inflammatory signaling, which is reciprocally fueled by aging-related alterations of physiology and metabolism. In the T cell compartment, aging contributes to T cell senescence and exhaustion, increased abundance of terminally differentiated cells, a corresponding attrition in naïve T cell numbers, and a decrease in the breadth of the receptor repertoire. Furthermore, inflammatory signaling drives aging-related pathologies and contributes to frailty in older individuals. Thus, there is growing evidence of biological aging modulating the efficacy and toxicity of T cell-mediated immunotherapies.Here, we review the available evidence from biological and clinical studies focusing on the relationship between T cell-mediated treatment of hematologic malignancies and age. We discuss biological features potentially impacting clinical outcomes in various scenarios, and potential strategies to improve the safety and efficacy of immune checkpoint inhibitors, T cell-engaging bispecific antibodies, and CAR-T cell therapy in older patients.